2006
DOI: 10.1021/jf053072o
|View full text |Cite
|
Sign up to set email alerts
|

Complete Quantification of Group A and Group B Soyasaponins in Soybeans

Abstract: A combination of high-pressure extraction and preparative chromatography was used to purify the group A and group B soyasaponins from soy germ for use as analytical standards and for use in biological assays. A standardized sample preparation and extraction method was developed for the analysis of phytochemicals found in soy and processed soy products, which is reproducible in other laboratories. The extracts can be analyzed with standard liquid chromatography-mass spectrometry and high-performance liquid chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 54 publications
0
58
1
3
Order By: Relevance
“…The group A soyasaponins are bisdesmosidic (Shiraiwa et al, 1991a) and are found predominantly in the germ of the seed, which accounts for only 3% of the total bean, resulting in low levels of this group in extracts from whole beans (about one fifth the level of group B soyasaponins). The group B soyasaponins are nearly equally distributed between the germ and the cotyledons of the seed (Shiraiwa et al, 1991b;Berhow et al, 2006)..…”
Section: Norwegian Scientific Committee For Food Safetymentioning
confidence: 99%
“…The group A soyasaponins are bisdesmosidic (Shiraiwa et al, 1991a) and are found predominantly in the germ of the seed, which accounts for only 3% of the total bean, resulting in low levels of this group in extracts from whole beans (about one fifth the level of group B soyasaponins). The group B soyasaponins are nearly equally distributed between the germ and the cotyledons of the seed (Shiraiwa et al, 1991b;Berhow et al, 2006)..…”
Section: Norwegian Scientific Committee For Food Safetymentioning
confidence: 99%
“…Soybeans have at least four different saponins (23). The saponins in the mature soybean are divided into group A and group B soyasaponins on the basis of their aglycone structures.…”
Section: Distribution-foaming Glycosidesmentioning
confidence: 99%
“…Soyasaponin은 비배당체(aglycone)인 soyasapogenol A, B, E 및 DDMP(2,3-dihydro-2,5-dihydroxy-6-methyl-4H-pyran-4-one)과 이들에 부착되는 당에 의하여 다양하게 분 류 된다 (Shiraiwa et al, 1991;Tsukamoto et al, 1993;Hu et al, 2002;Berhow et al, 2006). 일반적으로 soyasaponin 은 A계열 을 Aa, Ab, Ad, Ae, Af로 B계열은 DDMP가 부 착된 αg, βg, βa, γg, γa와 DDMP가 부착되지 않은 Ba, Bb, Bb', Bc로 E계열은 Bd와 Be로 구분하지만 (Decroos et al, 2005), 학자들에 따라 조금씩 다르게 명명되기도 한다 (Kitagawa et al, 1988a(Kitagawa et al, , 1988bYoshikoshi et al, 1996;Shibuya et al, 2010).…”
unclassified
“…콩의 isoflavone과 soyasaponin은 종실의 부위에 따라 함 량의 변이를 나타내는데, 이들 성분은 모두 배아가 종피와 자엽에 비해 함량이 월등히 높다. 일반적으로 isoflavone은 자엽에 0.13~0.35%, 배아는 0.97~2.07%가 함유되어 있으 며, soyasaponin은 콩 전체에 0.1~0.5%가 함유되어 있으 나, 부위별로 볼 때 자엽에 0.2~0.3%, 배아에 약 2% 함유 된 것으로 알려져 있다 (Kudou et al, 1992;Wang & Murphy, 1994;Anderson & Wolf, 1995;Berhow et al, 2006). Soyasaponin에 관한 연구는 지금까지 지속되고 있으 나 이들이 온도, pH 등에 불안정하고 다양한 형태로 존재하 여 분리 · 정제가 까다로운 물질로 알려져 있다 (Hu et al, 2002).…”
unclassified